The synthesis and characterization of 10,11-bis(hydroxyimino)-4,8,12,17-tetraaza 1,2,19,20-O-dicyclohexylideneoctacosene and some transition metal complexes - Tas, E; Çukurovali, A; Kaya, M (Gordon Breach Sci Publ Ltd, 1999)
In this study, a novel dioxime 10,11-bis(hydroxyimino)-4,8, 12,17-tetraaza-1,2,19,20-O-dicyclohexylideneoctacosene (LH2) has been synthesized starting from 1,2-O-cyclohexylidene-4-aza-8-aminooctane, which has been prepared from the 1-chloro-2,3-O-cyclohexylidene, and dichloroglyoxime. The structure of this vic-dioxime has been determined as the (E, Z) form according to H-1 NMR, C-13 NMR and IR data. Mononuclear complexes with a metal to ligand ratio of 1:2, except for UO2(VI), have been isolated with Co(III), Co(II), Cu(II) and Ni(II) salts. The metal to ligand ratio of the uranyl complex is 1:1 and it has a dimeric structure. Attempts to prepare trinuclear complexes of the ligand with Co(III), Co(II), Cu(II) and Ni(II), failed. The structure of the ligand and its complexes is proposed from elemental analyses, IR, UV-VIS,C-13 and H-1 NMR spectra, magnetic susceptibility measurements, thermogravimetric analyses (TGA) and differential thermal analyses (DTA).
Keywords: dioxime; transition metal complexes; uranyl